PENGARUH STRATEGI PEMASARAN DAN INOVASI PRODUK TERHADAP VOLUME PENJUALAN PRODUK WIFI.ID DI PT. TELKOM INDONESIA WILAYAH JAKARTA PUSAT - Dwi Putri Rustianti; Syahrul Reza (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the effect ofmarketing strategy and product innovation on the sales volume of Wifi.id products at PT. Telkom Indonesia Central Jakarta Area. The research method used is a quantitative method. Data collection techniques used in the form of questionnaires and literature. The population of this study are users of Wifi.Id products at PT.Telkom Indonesia, Central Jakarta Region. The sampling technique in this research is probability sampling with simple random sampling method. The sample is 75 samples. Analysis of the data used is multiple linear regression analysis using the help of IBM Statistics software version 24. The results showed that the influence of the marketing strategy variable had an effect on sales volume of 65.4%. While the product innovation variable has an effect of 84.8% on sales volume. The variables of marketing strategy and product innovation have a significant effect on sales volume at Telkom Indonesia in the Central Jakarta Region. The variables of marketing strategy and product innovation affect the sales volume variable simultaneously with a value of 0.860 or 86% of which 14% is explained by other variables not examined in this study.